BRAND IMAGE MEDIATES BETWEEN K-POP CELEBRITY ENDORSEMENTS IN SOCIAL MEDIA ADS AND THE PURCHASE INTENTION OF GEN Z CONSUMERS - Ajeng Aquinia; Bambang Sutejo; Rokh Eddy Prabowo (Jurnal Ekonomi, 2023)
The rapid movement of technology is growing significantly, especially in the smartphone industry. The number of several new brands of smartphones appearing in Indonesia makes tight competition between the previous smartphones brand. This phenomenon makes the fast movement to a brand by making great ads, especially in social media, and using celebrity endorsement as one of their strategy to attract new customers and boost the sales. This research is to find out that these strategies are still relevant to increase the sales of smartphones. The respondent of this research was generation Z who lived in Semarang and is currently active in using social media. The result of this research indicates that celebrity endorsement does play a significant role in effected brand image positively, but on the other hand celebrity endorsement does not influence purchase intenton. Brand image has a positive and significant effect on purchase intention. Brand image is capable to mediate between celebrity endorsement and purchase intention.